2019
DOI: 10.28959/jdpi.v30i1.4626
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Lampung Local Sand as Casting Sand in the Metal Casting Process

Abstract: In Indonesia especially sumatra island, the demands for casting sand was mainly fulfilled using sand brought from ceper, central Java although with a very expensive transportation cost. For the Sumatran region, the province of Lampung is rich in quartz sand that has the potential to act as substitute to the Java originated sand. This experiment aims to characterize sand from sub district Tanjung Bintang and sub district Maringgai of Lampung province as reference for its use as casting sand. In this experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hendro et al [136] used three different local sand named Ceper sand, Tanjung bintang sand, and Maringgai sand and evaluated clay content, grain fineness number, sand particle morphology, and chemical composition reported in Table 7 for the feasibility in sand mould casting. They observed that local sand could be used in sand mould casting, especially for non-ferrous casting.…”
Section: Other Waste Materialsmentioning
confidence: 99%
“…Hendro et al [136] used three different local sand named Ceper sand, Tanjung bintang sand, and Maringgai sand and evaluated clay content, grain fineness number, sand particle morphology, and chemical composition reported in Table 7 for the feasibility in sand mould casting. They observed that local sand could be used in sand mould casting, especially for non-ferrous casting.…”
Section: Other Waste Materialsmentioning
confidence: 99%